1995
DOI: 10.1002/chir.530070513
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of (R)‐ to (S)‐ketoprofen in eight animal species

Abstract: The (R)-enantiomer of the NSAID ketoprofen was administered orally at 20 mg/kg to a series of 8 animal species. In all species, a highly significant degree of inversion occurred after 1 h which varied from 27% (gerbil) to 73% (dog) and persisted or increased in plasma samples obtained 3 h after drug administration. Although the (R)-enantiomer was inactive as an inhibitor of cyclooxygenase, the analgesic effects of that isomer was almost the same as the (S)-isomer in animal analgesic assays, following oral admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…Chiral inversion of most NSAIDs proceeds in one direction-usually the R-enantiomer is transformed into the S-enantiomer. 16,27,28 Bidirectional inversion of both enantiomers was observed only sporadically. 29,30 Chiral inversion has been described not only for the 2-arylpropionates (profens), but also for 2-aryloxypropionates (oxyprofen herbicides) 16,31 and D-leucine.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Chiral inversion of most NSAIDs proceeds in one direction-usually the R-enantiomer is transformed into the S-enantiomer. 16,27,28 Bidirectional inversion of both enantiomers was observed only sporadically. 29,30 Chiral inversion has been described not only for the 2-arylpropionates (profens), but also for 2-aryloxypropionates (oxyprofen herbicides) 16,31 and D-leucine.…”
Section: Discussionmentioning
confidence: 91%
“…16 As with other enzymatic reactions, the quantitative course of chiral inversion also depends on a number of factors, such as the animal species. 27,39,40 Chiral analysis of residual substrate in the cultivation medium showed that R-(+)-F is converted into its respective antipode in hepatocytes. As a small amount of R-(+)-F was detected in hepatocytes from donor 4 incubated with S-(−)-F, the chiral inversion of S-(−)-F cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the effects of the pure enantiomers of ketoprofen on prostaglandin release from brain, ex vivo experiments cannot be performed in the rat since a high degree of bioinversion is observed when the (−)-R-enantiomer is administered orally. 13,14,21 Thus, for better comparison we assessed the effects of these compounds when brain portions were incubated in oxygenated Tyrode solution in the presence or absence of compounds at 37°C for 10 min, according to a procedure previously described elsewhere. 8 At this time point, PGF 2␣ production in the absence of inhibitor was significantly different from production at zero time, and inhibition by dexketoprofen was also significant.…”
Section: Stereoselective Inhibition Of Brain Coxmentioning
confidence: 99%
“…3 Previous work from our group suggested 80% and 10% chiral inversion for ketoprofen in rats 4 and humans, 5 respectively. Further, Aberg et al 6 found inversion of R-ketoprofen to its antipode in eight species. They classified the studied animals as either ''extensive'' (>50% inversion) or ''limited'' (<50%) inverters depending on their ability to invert R-ketoprofen.…”
Section: Introductionmentioning
confidence: 97%